«Kashenkin Lug»: Program for Consultative Psychological and Educational Support for Families Having Children with ASD. Evaluation of Efficiency - S.N. Pantsyr; E.L. Krasnoselskaya; K.K. Danilina; E.Y. Davydova; A.V. Khaustov (Moscow State University of Psychology and Education, 2021)
The article presents current understanding of consultation of children with autism spectrum disorders (ASD) in Russia along with the typical contexts in which families looking for help. The necessity of an integrated approach to the organization of consultations shown. We introduce a three-component program of psychological and educational support developed at the Federal Resource Center for Organization of Comprehensive Support to Children with ASD of MSUPE. The program includes a comprehensive psychological and educational examination, the development of an educational route and the feedback receiving, aimed at the analysis of the dynamics of development. The results of the evaluation of the effectiveness of the implementation of the program shown, demonstrating positive dynamics in the development of the child and the emerging needs of the family. We registered change in educational pathways as well as improvement of adaptive behavior. Additionally, we analyzed typical difficulties in following recommendations as reported by parents